The 3.4-3.5 Ga Sao Jose do Campestre massif, NE Brazil: remnants of the oldest crust in South America - Dantas, E. L.; Van Schmus, W. R.; Hackspacher, P. C.; Fetter, A. H.; Neves, BBD; Cordani, U.; Nutman, A. P.; Williams, I. S. (Elsevier B.V., 2004)
The oldest fragment of continental crust recognized in South America occurs as an isolated Archean enclave in northeastem Brazil's Borborema Province, ca. 600 Ma Brasiliano-Pan African orogenic belt. This Archean fragment, the Sao Jose do Campestre massif, is surrounded by large tracts of 2.2-2.0 Ga Paleoproterozoic gneisses and is located more than 600-1500 km from the much larger assemblages of Archean rocks found in the Sao Fransciso and Amazonian cratons, located to the south and west, respectively. Geochronological studies of the Sao Jose do Campestre massif show that its oldest rocks contain zircons with U-Pb ages up to 3.5 Ga and Sm-Nd T-DM model ages of more than 3.7 Ga, indicating that they represent reworked crust. This older nucleus is flanked by both reworked and juvenile 3.25 and 3.18 Ga rocks which arc intruded by both 3.00 and 2.69 Ga plutonic bodies. The protracted evolution the Sao Jose do Campestre massif is consistent with that of a larger continental mass as opposed to a small crustal fragment that grew in isolation. As such, the Sao Jose do Campestre massif is interpreted as representing a detached piece of an evolved craton that became entrained with younger rocks during a subsequent Paleoproterozoic accretionary-orogenic event. This hypothesis is bolstered by the presence of Paleoproterozoic gneisses that envelop the Sao Jose do Campestre massif, as well as the existence of ca. 2.0 Ga metamorphic zircon and monazite within its rocks. The occurrence of several different Archean cratonic basement inliers within the greater Paleoproterozoic crustal framework of the Borborema Province suggests that cratonic slices spalled off one or more larger Archean masses prior to the ca. 2.2-2.0 Ga Paleoproterozoic orogenic collage. A important challenge is to link these older fragments to their parent cratons. Although results are not unique, the pattern of ages and isotopic signatures observed in the Sao Jose do Campestre massif is similar to that seen in parts of the Sao Francisco Craton, and it is possible that the Sao Jose do Campestre massif is a fragment of an Archean continental fragment formed during an episode of continental breakup prior to 2200 Ma. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: early Archean; Borborema Province in NE brazil; SHIRIMP U-Pb